The MEOPAeDent trial protocol-an observational study of the Equimolar Mixture of Oxygen and Nitrous Oxide (EMONO) effects in paediatric dentistry - Tony Prud'homme; Sylvie Dajean-Trutaud; Morgane Rousselet; Fanny Feuillet; Marjorie Carpentier-Cheraud; Olivier Bonnot; Isabelle Hyon; Marie Grall-Bronnec; Serena Lopez-Cazaux; Caroline Victorri-Vigneau (BMC, 2019)
Abstract Background Many studies were conducted to assess the benefit/risk ratio of EMONO (Equimolar Mixture of Oxygen and Nitrous Oxide) in France before it was authorized for use outside the hospital setting in 2009. The main objective of this project is to evaluate the effects sought and felt by children when EMONO is used in paediatric dentistry. The secondary objectives are to (i) evaluate the appreciation of EMONO by the children, (ii) characterize children who experience both analgesia and anxiolysis, (iii) evaluate children's appetite for EMONO and characterize children with a high appetite and (iv) evaluate the impact of the difference in practice among the French dental service university hospitals on anxiety. The maintenance of a framework for the safe use of this drug, whose place in dental care is fundamental, is essential. Twelve of the 16 French dental service university hospitals agreed to participate in this study. Methods MEOPAeDent is an observational, descriptive, transversal study that aims to evaluate the effects sought and felt by children when EMONO is used in paediatric dentistry. Subjects requiring dental care under EMONO are recruited by 12 French dental service university hospitals. Patients aged from 3 to 15 years are recruited for the study when they visit a dental service of a French university hospital requiring dental care under EMONO. The investigator collects the necessary data from the child's medical records, from his own observations and from questions posed to the child and his/her parents. A survey is completed at the first and final sessions of dental care under EMONO. Discussion This study will provide an evaluation of the effects of EMONO on the French paediatric population in need of dental care as well as evaluate the appetite for the use of this substance. The results will first be used to provide additional data that is essential to monitor the use of a product with an authorization to use it outside of hospitals from 2009 in France, confirm its safety for use and justify its framework of application. Trial registration ClinicalTrials.gov ID: NCT03453411 registered 2 March 2018.